A Framework for Economic Evaluation of Highway Development Projects Based on Network-Level Life Cycle Cost Analysis - Ziari, Hassan; Behbahani, Hamid; Amini, Amir Ali (Promet - Traffic&Transportation, 2015)
For economic evaluation of a highway development project, multiple criteria must be considered on a timeframe longer than the project implementation interval and a geographical area larger than the project zone. In this study, a framework is proposed based on the Network-Level Life Cycle Cost Analysis (NL-LCCA) to assess the effect of highway development projects on mobility, safety, economy, environment and other monetizable criteria. In this approach, project impacts are estimated within physical boundaries of highway network over the network life cycle. This framework can be used as a decision-making support for evaluation and ranking of pre-defined development projects, proposing new cost-effective development projects, assessment of cost efficiency of existing highway network and budget allocation optimization.